Occupational factors affecting sick leave attributed to low back pain - Wickström, G. J.; Pentti, Jaana (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'The purpose of this study was to determine the occupational factors that cause workers to take sick leave.' ' METHODS ': 'Twice, with a 24-month interval, 117 white- and 189 blue-collar employees from 2 metal industry companies completed a questionnaire on recurrent low-back pain and exposure to potential risk factors (biomechanical loads, physical environment, psychosocial factors) at work. Sick leave was monitored for the period between the questionnaires.' ' RESULTS ': 'Low-back pain was predicted by exposure to harmful biomechanical loads among both white- and blue-collar workers [odds ratio (OR) 4.1 and 4.7, respectively), stress among white-collar workers (OR 2.4), and draft among blue-collar workers (OR 2.3). The take-up of sick leave was predicted by exposure to harmful biomechanical loads [rate ratio (RR) 1.7]; for sick leaves attributed to low-back pain the rate ratio was 3.1. Lack of recognition and respect at work predicted sick-leave attributed to low-back pain (RR 2.0), but not to other disorders.' ' CONCLUSION ': 'Recurrent low-back pain is preceded by reports of harmful biomechanical loads at work among white- and blue-collar workers, by stress among white-collar workers and by draft among blue-collar workers. The environmental and psychosocial factors under study did not modify the relation between biomechanical loads and the recurrent low-back pain. Sick leave attributed to back disorders is preceded by exposure to biomechanical loads at work and by a lack of recognition and respect at work among blue-collar workers. Biomechanical loading seems to be the most important occupational factor predicting both recurrent low-back pain and sick leave attributed to back disorders. Lack of recognition and respect at work appear to affect sick leave attributed to back disorders.
Keywords: biomechanical load; physical environment; psychosocial load; respect at work; sickness absence